Struktur Pemikiran dan Gerakan Islam Kontemporer - Huda, Sokhi (AL-TAHRIR, 2018)
Abstract: The contemporary era of the Islamic world is characterized by a passion for building its own life. This spirit encounters a number of new problems at both internal and external levels. Hence, the variations of Islamic progressive thought and movement emerged to provide solutions to these problems. This variation exhibits its distinctive character and can be shaped into a general pattern of structures composed of five aspects and fourteen components. The ideotheological aspect base consists of the principal sources and joints of Islam and prophethood. The methodological spectrum aspect consists of the legacy of Islamic tradition, law, and methodology. The aspect of ideality concept consists of the concepts of Islam and Muslims and the concepts of comparison of Islam and its treasures. The aspects of action zone consist of behavior, science and technology, politics, and social interaction. The aspects of reality and solutions consist of the reality of Islam and Muslims, the problems of Muslims, and progressive solutions. All these aspects and components move in a hierarchical and circular manner. Hierarchical motion shows the vertical-interactive relation from the highest level to the lowest level. Circular motion shows the referential relation of the lowest level that seeks to trace its sources at the highest level for the fulfillment of progressive solutions with reinterpretative and historical approaches.Ù…Ù„Ø®Øµ: ØªØªÙ…ÙŠØ² Ø§Ù„Ø¹ØµØ± Ø§Ù„Ù…Ø¹Ø§ØµØ± ÙÙŠ Ø§Ù„Ø¹Ø§Ù„Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø¨Ø´ØºÙ Ù„Ø¨Ù†Ø§Ø¡ ØÙŠØ§ØªÙ‡ Ø§Ù„Ø®Ø§ØµØ©. ÙˆØªÙˆØ§Ø¬Ù‡ Ù‡Ø°Ù‡ Ø§Ù„Ø±ÙˆØ Ø¹Ø¯Ø¯Ø§ Ù…Ù† Ø§Ù„Ù…Ø´Ø§ÙƒÙ„ Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© Ø¹Ù„Ù‰ Ø§Ù„ØµØ¹ÙŠØ¯ÙŠÙ† Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠ ÙˆØ§Ù„Ø®Ø§Ø±Ø¬ÙŠ. ÙˆÙ…Ù† Ù‡Ù†Ø§ Ø¸Ù‡Ø±Øª Ø§Ø®ØªÙ„Ø§ÙØ§Øª Ø§Ù„ÙÙƒØ± Ø§Ù„ØªÙ‚Ø¯Ù…ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ÙˆØ§Ù„ØØ±ÙƒØ© Ù„ØªÙ‚Ø¯ÙŠÙ… ØÙ„ÙˆÙ„ Ù„Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø´Ø§ÙƒÙ„. ÙˆÙŠØ¸Ù‡Ø± Ù‡Ø°Ø§ Ø§Ù„Ø§Ø®ØªÙ„Ø§Ù Ø·Ø§Ø¨Ø¹Ù‡ Ø§Ù„Ù…Ù…ÙŠØ² ÙˆÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠØªØ´ÙƒÙ„ ÙÙŠ Ù†Ù…Ø· Ø¹Ø§Ù… Ù„Ù„Ù‡ÙŠØ§ÙƒÙ„ Ø§Ù„Ù…ÙƒÙˆÙ†Ø© Ù…Ù† Ø®Ù…Ø³Ø© Ø¬ÙˆØ§Ù†Ø¨ ÙˆØ£Ø±Ø¨Ø¹Ø© Ø¹Ø´Ø± Ù…ÙƒÙˆÙ†Ø§. ØªØªÙƒÙˆÙ† Ù‚Ø§Ø¹Ø¯Ø© Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„Ø£ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠ Ù…Ù† Ø§Ù„Ù…ØµØ¯Ø± ÙˆØ§Ù„Ù…ÙØµÙ„ Ø§Ù„Ø£Ø³Ø§Ø³ÙŠ Ù„Ù„Ø¥Ø³Ù„Ø§Ù… ÙˆØ§Ù„Ù†Ø¨ÙˆØ©. ÙˆÙŠØªØ£Ù„Ù Ø¬Ø§Ù†Ø¨ Ø§Ù„Ù…Ù†Ù‡Ø¬ÙŠØ© Ù…Ù† ØªØ±Ø§Ø« Ø§Ù„ØªÙ‚Ø§Ù„ÙŠØ¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆØ§Ù„Ù‚Ø§Ù†ÙˆÙ† ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ÙŠØ©. Ø¥Ù† Ù…ÙÙ‡ÙˆÙ… Ù…ÙÙ‡ÙˆÙ… Ø§Ù„Ù…Ø«Ø§Ù„ÙŠØ© ÙŠØªÙƒÙˆÙ† Ù…Ù† Ù…ÙØ§Ù‡ÙŠÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ÙˆØ§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙˆÙ…ÙØ§Ù‡ÙŠÙ… Ø§Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ÙˆÙƒÙ†ÙˆØ²Ù‡. ÙˆØªØªØ£Ù„Ù Ø¬ÙˆØ§Ù†Ø¨ Ù…Ù†Ø§Ø·Ù‚ Ø§Ù„Ø¹Ù…Ù„ Ù…Ù† Ø§Ù„Ø³Ù„ÙˆÙƒ ÙˆØ§Ù„Ø¹Ù„ÙˆÙ… ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ ÙˆØ§Ù„Ø³ÙŠØ§Ø³Ø© ÙˆØ§Ù„ØªÙØ§Ø¹Ù„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ. ÙˆØªØªÙƒÙˆÙ† Ø¬ÙˆØ§Ù†Ø¨ Ø§Ù„ÙˆØ§Ù‚Ø¹ ÙˆØ§Ù„ØÙ„ÙˆÙ„ Ù…Ù† ÙˆØ§Ù‚Ø¹ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ÙˆØ§Ù„Ù…Ø³Ù„Ù…ÙŠÙ†ØŒ ÙˆÙ…Ø´Ø§ÙƒÙ„ Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ†ØŒ ÙˆØ§Ù„ØÙ„ÙˆÙ„ Ø§Ù„ØªÙ‚Ø¯Ù…ÙŠØ©. ÙƒÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ø¬ÙˆØ§Ù†Ø¨ ÙˆØ§Ù„Ù…ÙƒÙˆÙ†Ø§Øª ØªØªØØ±Ùƒ Ø¨Ø·Ø±ÙŠÙ‚Ø© Ù‡Ø±Ù…ÙŠØ© ÙˆØ¯Ø§Ø¦Ø±ÙŠØ©. Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ù‡Ø±Ù…ÙŠØ© ØªØ¸Ù‡Ø± Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ø¹Ù…ÙˆØ¯ÙŠØ© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ù…Ù† Ø£Ø¹Ù„Ù‰ Ù…Ø³ØªÙˆÙ‰ Ø¥Ù„Ù‰ Ø£Ø¯Ù†Ù‰ Ù…Ø³ØªÙˆÙ‰. Ø§Ù„ØØ±ÙƒØ© Ø§Ù„Ø¯Ø§Ø¦Ø±ÙŠØ© ØªØ¸Ù‡Ø± Ø§Ù„Ø¹Ù„Ø§Ù‚Ø© Ø§Ù„Ù…Ø±Ø¬Ø¹ÙŠØ© Ù…Ù† Ø£Ø¯Ù†Ù‰ Ù…Ø³ØªÙˆÙ‰ ØªØØ§ÙˆÙ„ ØªØªØ¨Ø¹ Ù…ØµØ§Ø¯Ø±Ù‡Ø§ Ø¹Ù„Ù‰ Ø£Ø¹Ù„Ù‰ Ù…Ø³ØªÙˆÙ‰ Ù„ØªØÙ‚ÙŠÙ‚ Ø§Ù„ØÙ„ÙˆÙ„ Ø§Ù„ØªÙ‚Ø¯Ù…ÙŠØ© Ø¨Ù…Ù†Ù‡Ø¬ Ø¥Ø¹Ø§Ø¯Ø© Ø§Ù„ØªÙØ³ÙŠØ± ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ.Abstrak: Era kontemporer dunia Islam ditandai oleh semangat untuk membangun kehidupannya sendiri. Semangat ini menghadapi sejumlah problem baru pada level internal maupun eksternal. Oleh karena itulah muncul variasi pemikiran dan gerakan progresif dunia Islam untuk memberikan solusi terhadap problem-problem tersebut. Variasi ini memperlihatkan karakter khasnya dan dapat dibentuk ke pola umum struktur yang tersusun atas lima aspek dan empat belas komponen. Aspek basis ideoteologis terdiri atas sumber dan sendi pokok Islam dan kenabian. Aspek spektrum metodologi terdiri atas warisan tradisi Islam, hukum, dan metodologi. Aspek konsep idealitas terdiri atas konsep-konsep tentang Islam dan muslim dan konsep-konsep perbandingan tentang Islam dan khazanahnya. Aspek zona aksi terdiri atas keperilakuan, sains dan teknologi, politik, dan interaksi sosial. Aspek realitas dan solusi terdiri atas realitas Islam dan muslim, problem-problem umat Islam, dan solusi progresif. Semua aspek dan komponen ini bergerak secara hirarkis dan sirkular. Gerak hirarkis menunjukkan relasi vertikal-interaktif dari level tertinggi sampai level terendah. Gerak sirkular menunjukkan relasi referensial dari level terendah yang berusaha untuk melacak sumbernya pada level tertinggi untuk pemenuhan solusi progresif dengan pendekatan reinterpretatif dan historis.Â